2014
DOI: 10.1590/s1984-29612014050
|View full text |Cite
|
Sign up to set email alerts
|

Lectin, hemolysin and protease inhibitors in seed fractions with ovicidal activity against Haemonchus contortus

Abstract: Bioactive molecules of plant species are promising alternatives for the chemical control of gastrointestinal nematodes in ruminants. Extracts of native and exotic seed species from Brazil's semi-arid region were tested in vitro in an egg hatch assay and the bioactivity of their proteins was investigated. Each seed species was subjected to three extractions with three types of solvents. All the seeds showed ovicidal activity, which varied according to the solvents. Higher ovicidal activity was found in the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Mashela & Nthangeni (2002) observed that castor used in soil favoured the growth of tomato, without affecting soil pH, and suppressed the nematode Meloidogyne incognita. In addition, ovicidal activity against Haemonchus contortus was already detected in fractions of the seed extracts of Ricinus communis by Salles et al (2014). This present work shows that castor cake controls the free-living stage of small ruminant nematodes in vitro and has the additional benefit of nourishing the plant.…”
Section: Discussionsupporting
confidence: 62%
“…Mashela & Nthangeni (2002) observed that castor used in soil favoured the growth of tomato, without affecting soil pH, and suppressed the nematode Meloidogyne incognita. In addition, ovicidal activity against Haemonchus contortus was already detected in fractions of the seed extracts of Ricinus communis by Salles et al (2014). This present work shows that castor cake controls the free-living stage of small ruminant nematodes in vitro and has the additional benefit of nourishing the plant.…”
Section: Discussionsupporting
confidence: 62%
“…A previous study reported that the crude water extract of Moringa oleifera seed showed high egg hatch inhibition on Haemonchus contortus [52]. The results of this work describe a potential use of Moringa oleifera in controlling nematode parasites [53].…”
Section: Schistosomiasis Is a Chronic Tropical Disease Caused By Parasupporting
confidence: 58%
“…Although secondary metabolites have been extensively correlated with nematicidal effects, demonstrating their applicability to controlling the gastrointestinal nematodes of small ruminants, plant proteins represent a novel approach for controlling these parasites (SALLES et al, 2014). The use of therapeutic proteins is one of the fastest growing sectors in the pharmaceutical market and has undergone several generations of development to achieve increasingly viable commercial products.…”
Section: Discussionmentioning
confidence: 99%